Post-COVID-19 Infection; Paediatric Multisystemic Inflammatory Syndrome in an 8-Month-Old Infant - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
The coronavirus disease 2019 (COVID-19) associated with multisystem inflammatory syndrome in children and adolescents is an emerging challenge and has been described as a new dangerous childhood disease that is temporally associated with COVID-19. An 8-month-old infant presented with unrelenting fever of 2 weeks, associated non-purulent conjunctivitis, redness of the lips and tongue, as well as tenderness, swelling and desquamation of the palms and digits and diarrhoea. She also had associated irritability, refusal to feed and poor sleep. She had positive polymerase chain reaction (PCR) COVID-19 test 3 months earlier. However, a repeat PCR test was negative at presentation. She had raised erythrocyte sedimentation rate of 85 mn/h, good systolic function on echocardiogram with normal rhythm electrocardiogram. She was diagnosed with post-COVID-19 paediatric multisystemic inflammatory syndrome and treated with intravenous immunoglobulin, oral prednisolone and aspirin. Patient symptoms improved significantly after 72 h of treatment. Therefore, a high index of suspicion is required in all children presenting with unexplained fever.